Brain natriuretic peptide and all-cause mortality in patients treated with haemodialysis - Maria K Svensson; Rita Nassar; Jan Melin; Magnus Lindberg; Hans Furuland; Jenny Stenberg (BMC Nephrology, 2025)
Abstract Background Brain natriuretic peptide (BNP) is a hormone secreted from the heart in response to fluid overload. In patients with chronic kidney disease (CKD), inadequate fluid management during haemodialysis may cause fluid overload and overhydration (OH), risk factors for mortality. The aim of this exploratory pilot study was to analyse the relationships between BNP, OH and all-cause mortality in patients with CKD and haemodialysis. Methods In this prospective observational study, five-year survival was analysed in 64 patients with CKD and haemodialysis. Bivariate correlations were performed to analyse the relationships between BNP, OH, and all-cause mortality. Cox regression analysis was performed to adjust the relationship between BNP and all-cause mortality for selected clinical and biochemical characteristics, collected at baseline. Results By the end of the study, 33 patients (52%) had died. In bivariate correlation analysis age (r = 0.38), BNP (r = 0.48), handgrip strength (r=-0.34), lean tissue index (r=-0.41) and CRP level (r=-0.34, p = 0.007) were significantly associated with all-cause mortality. In a linear regression model, BNP was found to be a significant predictor of all-cause mortality (HR 2.61). However, after adjusting for age, handgrip strength, and CRP, BNP was no longer a statistically significant predictor of all-cause mortality. Instead, age, handgrip strength and CRP were significant predictors of all-cause mortality (HR 1.04; HR 0.95 and HR 2.61, respectively). Conclusions In this study, BNP was correlated with all-cause mortality in patients with CKD and haemodialysis, but OH was not. When adjusting for other clinical and biochemical factors, age, inflammation, and handgrip strength were found to be independent and more important predictors of all-cause mortality than BNP.